Pemberdayaan Kader Posyandu dalam Pemberian ASI Eksklusif - Nurbaiti Nurbaiti; Gustina Gustina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Exclusive breastfeeding is the best food for infants breast milk (breast milk) is given for 6 months without other additional food and continued until the age of 2 years, breastfeeding can reduce infant mortality and can increase growth and development in children. at this time there are still many mothers who do not give exclusive breast milk to their babies. Based on data obtained by one of the health centers in Jambi from 111 babies who were given exclusive breast milk 63 babies and who did not give exclusive breastfeeding 28 babies, although most have given exclusive breast milk there are still babies who are not given exclusive breast milk, this can be influenced by the condition of mothers who work outside the home that makes the mother can not breastfeed her baby beside the mother's knowledge of the importance of exclusive breast milk is still not optimal, the busyness of working mothers makes mothers prefer formula milk that is more practical for the baby. Related to the problem, it is necessary to empower cadres so that cadres can play an active role in providing information to mothers who are in the integrated service center area. This service is done to improve the knowledge, understanding, and skills of integrated service center cadres. This activity was carried out in the Working Area of Simpang Kawat Health Center held in March to August 2020, the target in this activity posyandu cadres use the method of lectures, discussions, question and answer with leaflet media and laptop. As a result of this activity increased the knowledge, understanding, and skills of cadres about exclusivebreast milk and will be published in the form of journals to be easily accessed by the community.